Francis M. Macatangay - Francisco-Javier Ruiz-Ortiz (eds.), Ben Sira in Conversation with Traditions. A Festschrift for Prof. Núria Calduch-Benages on the Occasion of her 65th Birthday (Deuterocanonical and Cognate Literature Studies 47; Walter de Gruyter - Morla Asensio, Víctor (Estudios bíblicos, 2023)
Publicación cuatrimestral de referencia internacional en estudios bíblicos, editada por la Universidad San Dámaso en colaboración con la Asociación Bíblica Española.